Determinación de infecciones de vías urinarias y su relación con los factores desencadenantes en mujeres de edad fértil de la Parroquia Buenavista Cantón Chaguarpamba. - Peralta Córdova, Karina Ivanova (2013)
Urinary tract infections are a public health problem that affects to the general population. According to the World Health Organization, 30% of women have ever had this kind of infection during their reproductive age, in Ecuador according to the INEC ranks eighth among the causes of disease, it was the main reason for which this research was made. It was called:: DETERMINATION OF URINARY TRACT INFECTIONS AND ITS RELATIONSHIP WITH TRIGGERS IN FERTILE AGE WOMEN OF BUENAVISTA TOWN, IN CHAGUARPAMBA CANTON,I made a prospective research of Descriptive kind of cross section, as it was implemented in a period time and allowed us to determine the different social, cultural, physiological factors and its relationship with the incidence of urinary tract infections in fertile age woman. 118 samples were analyzed in asymptomatic women, of whom 39 patients (46%) had urinary tract infection verified by urinalysis and urine cultivation, It help to identifying the causal agents in order of frequency: Escherichia Coli 59%, Enterobacter spp 28%, Staphylococcus saprophyticus 7%, Proteus Vulgaris 3% y Citrobacter freundii 3%. The triggers factors in the development of pathology in the urinary tract were: poor personal hygiene, use of intra-vaginal devices, inadequate underwear, promiscuity, onset of early sexual life, pregnancy, piped water, colonization of bacteria, among the most important. Finally it was possible looked for medical care and treatment to patients who required it, the patients received preventive educational lectures in order to raise awareness of the risk that can cause infections in the urinary tract. Key words: Incidence, infections, urinary tract, urinalysis, urine cultivation